DISAIN GEOMETRI REAKTOR FOTOSEL CAHAYA RUANG - Rahadian Zainul; Admin Alif; Hermansyah Aziz; Syukri Arief; Syukri - (Universitas Andalas, 2015)
This research aims to obtain reactor design photocells that can convert light energy into electrical energy space. Room light energy derived from sunlight that comes into the room and fluorescent light irradiation. Photocells reactor using a panel of copper oxide (Cu2O/CuO) of calcined Cu plate and filler electrolyte Na2SO4 0.5 N. The design of the geometry of the reactor photocells covering thickness of the glass pane, the distance between the electrodes, the interface layer, layer and coating reflector panels, and junction type np used. Reactor photocells 1 (R1) and 2 (R2) is identical in geometry to the thickness of the glass panel 3 mm thick reactor 15 mm without anti reflector, but the difference at the junction of type n, (R1 = plate Cu; R2 = plate Aluminum) generate 182.82 mW/m2 and 21119644.3 NW/m2. Design R3 (junction-type n = plate Cu) and R4 (junction-type n = plate Al), a panel thickness of 15 cm and has a layer anti reflector provide power 214.95 mW/m2 and 24163298.3 NW/m2. Design Reactor 5 (R5 = Cu) and R6 (Al), thickness of 9 mm, the distance between the electrodes 0:30 mm, using anti reflector carbon, giving each the power of 277.36 mW/m2 and 31258420.91 NW/m2. The most optimum reactor design is the design of R6 with 2:14% conversion capabilities (Intensity = 90.21 foot candles) for the sunlight into the room.